2011
DOI: 10.3109/01902148.2011.620680
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 mediates pulmonary vascular permeability in a two-hit model of ventilator-associated lung injury

Abstract: To test the hypothesis that IL-6 contributes to the development of ventilator-associated lung injury (VALI), IL-6-deficient (IL6−/−) and wild-type control (WT) mice received intratracheal hydrochloric acid followed by randomization to MV (MV+IT HCl) or spontaneous ventilation (IT HCl). After 4 hr, injury was assessed by estimation of lung lavage protein concentration and total and differential cell counts, wet/dry lung weight ratio, pulmonary cell death, histologic inflammation score (LIS), and parenchymal mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 61 publications
(68 reference statements)
1
41
1
Order By: Relevance
“…23 Moreover, it is suggested that IL-6 could be a reasonable therapeutic target for VILI not only for its antiinflammatory effect. 24 IL-6 geneYdeficient mice exhibit a markedly improved pulmonary vascular permeability when compared with a wild-type control in a rodent model of VILI, 24 and this protective effect of IL-6 is inflammation independent, 24 suggesting that IL-6 may also play a vital role on barrier dysfunction in VILI. Our data are consistent with previous studies, the elevated IL-6 production was accompanied by barrier dysfunction and lung edema.…”
Section: Discussionmentioning
confidence: 98%
“…23 Moreover, it is suggested that IL-6 could be a reasonable therapeutic target for VILI not only for its antiinflammatory effect. 24 IL-6 geneYdeficient mice exhibit a markedly improved pulmonary vascular permeability when compared with a wild-type control in a rodent model of VILI, 24 and this protective effect of IL-6 is inflammation independent, 24 suggesting that IL-6 may also play a vital role on barrier dysfunction in VILI. Our data are consistent with previous studies, the elevated IL-6 production was accompanied by barrier dysfunction and lung edema.…”
Section: Discussionmentioning
confidence: 98%
“…IL-lβ, whether administered systemically or locally into the pulmonary parenchyma, can acutely increase pulmonary substance P (SP) and vascular permeability, possibly via stimulating PCFs [49]. Gurkan et al [50] reported that genetic deletion of IL-6 significantly attenuated alveolar-capillary barrier disruption in a two-hit model of acute lung injury. In this study, AMPK activation protected against lung barrier dysfunction induced by both high glucose and LPS stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the role of IL-6 in lung injury 66, 7274 . IL-6 had been previously associated with increased mortality in ARDS 75, 76 and in acute kidney injury in critically ill patients 77 .…”
Section: Pathogenetic Mechanisms Of Experimental Ardsmentioning
confidence: 99%